Importance of hipnoterapy in dyadic adjustment and mood disorders post-pandemic - Cravo Barata, Nuno (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
The present study sought to evaluate the effect of the hypnotherapeutic intervention model in the treatment of symptoms leading to a diagnosis of anxiety and depression and to evaluate the dyadic adjustment in patients exposed to COVID-19. Therefore, this study is classified as a quantitative cross-sectional descriptive and correlational in order to acquire a better understanding of the importance of the hypnotherapeutic procedure in reducing symptoms related to anxiety and depression and the quality of dyadic adjustment.The results revealed the specific benefits of hypnosis in the reduction of symptomatology associated with mood disorders and in the quality of dyadic adjustment.